2014
DOI: 10.1016/j.jval.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Analysis of Sensor-Augmented Insulin Pump Therapy and Automated Insulin Suspension versus Standard Pump Therapy for Hypoglycemic Unaware Patients with Type 1 Diabetes

Abstract: Based on the Australian experience evaluating new interventions across a broad range of therapeutic areas, sensor-augmented insulin pump therapy with LGS may be considered a cost-effective alternative to standard pump therapy with self-monitoring of blood glucose in hypoglycemia unaware patients with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 30 publications
(50 reference statements)
0
23
0
3
Order By: Relevance
“…They found that the cost per QALY was AUS$40 803 in patients ≥12 years. 69 Finally, Graham and colleagues, modeling the cost saving of RT-CGM using the same assumptions noted above, [10][11][12][13][14][15][16] found that RT-CGM reduced the yearly cost of hypoglycemia by 13% in a population of 10 million insured patients. 70 The cost-effectiveness of using RT-CGM in patients with type 2 diabetes not on prandial insulin was evaluated by Fonda and colleagues.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…They found that the cost per QALY was AUS$40 803 in patients ≥12 years. 69 Finally, Graham and colleagues, modeling the cost saving of RT-CGM using the same assumptions noted above, [10][11][12][13][14][15][16] found that RT-CGM reduced the yearly cost of hypoglycemia by 13% in a population of 10 million insured patients. 70 The cost-effectiveness of using RT-CGM in patients with type 2 diabetes not on prandial insulin was evaluated by Fonda and colleagues.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Moreover, the inputs related to the device's effectiveness used in this paper pertained to the findings of a systematic literature review and meta‐analyses conducted by our research team and that included all relevant evidence available to date. The values obtained were somewhat lower than the effectiveness values used in other cost‐effectiveness analyses . Transition probabilities have, moreover, been collected from more recent literature both for T1DM and T2DM patients (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 87%
“…33 In the past decade, eight publications have examined the cost-effectiveness of the RT-CGM in patients with T1DM (Table 2). [34][35][36][37][38][39][40][41] The results of these studies are presented in terms of cost per qualityadjusted life year (QALY) or cost per hypoglycemic event avoided. Results are wide ranging, possibly because of differences in assumptions that form the basis of the models.…”
Section: Cost and Evidence Of Cost-effectivenessmentioning
confidence: 99%
“…It is important to note that only two of the eight published CEAs evaluated standalone RT-CGM, 34,37 whereas others evaluated sensor-augmented pump therapy 35,36,[38][39][40][41] ; the CEA performed by Huang et al was based on outcomes from the Juvenile Diabetes Research Foundation trial, in which intervention group patients could have received either sensoraugmented insulin pump therapy or MDIs plus RT-CGM.…”
Section: Cost and Evidence Of Cost-effectivenessmentioning
confidence: 99%